Economic Contributions of Tribal Markets in Nagaland: A Kohima-Centric Study - Kenye, Riweu; Faishal, Mohd (Journal of Current Social Issues Studies, 2025)
Tribal markets in Nagaland are crucial elements of the region's socio-economic structure, especially in Kohima, where these markets offer substantial chances for income generation, informal employment and livelihoods diversification. This research studies economic impacts of these markets by collecting primary data from 112 participants by using the structured questionnaires. The analysis of the data was carried out using descriptive statistics, Chi-square tests, and ordinal logistic regression. The findings indicate that many vendors depend on these markets as either a main or additional source of income, with significant correlations between income levels and factors such as the type of products sold, gender of the vendors, and the frequency of market participation. Increased income outcomes were associated with regular engagement and sale of value-added products. Whereas they play a role in community sustainability, tribal markets face ongoing issues such as the insufficient infrastructure, restricted access to finance, and lack of formal policy recognition. The findings emphasize the importance of integrating informal economies into urban planning and financial inclusion efforts, providing specific empirical insights from Kohima to the broader academic discourse. This study advocates for the creation of inclusive policy frameworks that will recognize and enhance the role of tribal markets in supporting regional development.
Keywords: Indigenous livelihoods; informal economy; Northeast India; ordinal regression; income generation; Tribal markets